Human Security Dalam Kontra-Terorisme Melalui Whole of Government dan Whole of Society: Studi Kasus Implementasi RAN PE 2021-2025 - Afnia Sari; Wachid Ridwan (Jurnal Keamanan Nasional, 2026)
The emergence of violent extremism as a prominent non-traditional security threat has driven a fundamental shift in security governance, transitioning from state-centric, coercive approaches toward preventive and collaborative models. In Indonesia, this transformation is institutionalized through the National Action Plan on Preventing and Countering Violent Extremism Leading to Terrorism (RAN PE) 2021–2025, which operationalizes Whole-of-Government (WoG) and Whole-of-Society (WoS) approaches. Employing a constructivist perspective, this study examines how global norms of Human Security and Preventing Violent Extremism (PVE) are diffused and localized into Indonesia’s domestic security practices through state–civil society interactions. The study finds that while the RAN PE marks a significant evolution from a predominantly law enforcement-oriented model toward a preventive, community-based governance architecture, implementation remains shaped by enduring state-centric security logics. Civil Society Organizations (CSOs) act as key norm entrepreneurs, strengthening social cohesion, peace education, and community resilience while translating global norms into locally contextualized practices. Consequently, the RAN PE represents both a strategic policy shift and a structural negotiation between state and non-state actors over contemporary security governance. This paper contributes to the P/CVE literature by illustrating how the interplay between WoG and WoS frameworks mediates norm localization, underscoring the critical role of institutionalized state–civil society collaboration for sustainable, preventive security governance.